Islamised English Language Teaching (ELT) Materials as Culturally Responsive Pedagogy: A Systematic Review - Ainol Mardhiah; Hayatul Muna; Diana Purwati; Sari Diana (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
This systematic review examines the conceptualisation, pedagogical benefits, and challenges of Islamised English Language Teaching (ELT) materials in Muslim educational contexts. Using the PRISMA framework, 24 peer-reviewed studies published between 2022 and 2026 were systematically identified from Google Scholar. The review included empirical journal articles on Islamised ELT materials or the integration of Islamic values into English language teaching, while books, conference proceedings, theses, dissertations, review articles, inaccessible publications, and non-ELT studies were excluded. The selected timeframe captures recent developments in culturally responsive pedagogy and the growing interest in contextualising English education within Muslim educational settings. The findings show that Islamised ELT materials are generally viewed as culturally responsive resources that integrate Islamic values, learners’ identities, and local contexts into English learning while still supporting global communication. The reviewed studies indicate that these materials can enhance students’ motivation, engagement, identity affirmation, character development, and contextualised learning experiences. They also encourage more reflective and value-based teaching practices. However, challenges remain such as limited teacher preparation, lack of contextualised resources, rigid curricula, and concerns about balancing local values with global perspectives. The review suggests that Islamised ELT materials have strong potential to make English learning more meaningful and relevant for Muslim learners when supported by appropriate material design, teacher training, and institutional support.